KEBIJAKAN FISKAL PEMERINTAH DALAM UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT INDONESIA - Mahpud Sujai (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Fiscal policy plays an important role in the implementation of government functions. One of the functions of the government under the constitution is to promote the general welfare and intellectual life of the nation. Therefore, this paper aims to explore the government's fiscal policies and budgetary allocations in order to improve the welfare of the community with a focus on poverty reduction, education, infrastructure and food security which is the number of pillars that must be achieved to meet the millennium development goals (MDGs) that has been agreed. The methodology used is descriptive analysis method accompanied by literature review and data analysis. Government effort on fiscal policy has been showed results with continued growth of the Indonesian economy, reduced the number of the poor, food security and increased education and infrastructure. This has resulted in improved community welfare that can be seen from the Human Development Index (HDI) which continues to improve. The Government should continue implementing pro-poor policy by continuing to prioritize fiscal policy and budget allocation for development activities.